Influence of structure and composition in the mechanical properties of textile polymeric fabrics. Issue 4 (May 2019) - dos Santos, Thiago Felix; da Silva Santos, Caroliny Minely; da Fonseca, Rubens Tavares; dos Santos, Vinicius Silva; Grosschopf, Mariana Guisdana; de Aquino, Marcos Silva
Knitting is a very important textile sector in the area of technological development and also for the economy. The knitted have special characteristics that allow their use in different situations. To use them with better use, it is important to know what these properties are and so apply them for a particular purpose. This work investigates several types of knitted 100% cotton and blend 67% cotton/33% polyester and evaluates its behavior when subjected to mechanical analysis (friction, abrasion, and traction) under the respective standards ASTM D 4970 adapted to ISO 12945-2 and ASTM D 5034. The obtained results show that, for the mechanical properties analyzed, the types of loops present in the structure and the composition of the knitted are fundamental factors for optimizing stress and strain as well as reducing mass loss and the propensity to pilling formation. The double piquet structures have a higher sensitivity to the tests, especially when we insert the polyester synthetic polymer that significantly alters the mechanical behavior.